What Are Governments Spending on Health in East and Southern Africa? - Piatti-Funfkirchen, Moritz; Lindelow, Magnus; Yoo, Katelyn (Taylor and Francis, 2019)
Progress toward universal health care (UHC) in Africa will require sustained increases in public spending on health and reduced reliance on out-of-pocket financing. This article reviews trends and patterns of government spending in the East and Southern Africa regions and points out methodological challenges with interpreting data from the World Health Organization’s (WHO) Global Health Expenditure Database (GHED) and other sources.